Embedding evidence-based practice in speech and language therapy : international examples - Roddam, Hazel; Skeat, Jemma; Wiley InterScience (Online service) (Oxford : Wiley-Blackwell, 2010)
Like all health professionals, speech and language therapists (SLTs) need to keep themselves up-to-date with the research evidence base that is relevant to their field of practice and be able to show how this contributes to their clinical decision-making. However, it is not always clear to practitioners how evidence-based practice (EBP) can be properly embedded in their day-to-day activities. In this valuable book, Hazel Roddam and Jemma Skeat present a wealth of instructive examples by SLT contributors from around the world, showing how clinicians, educators, and researchers have risen to the EBP challenge. Embedding evidence-based practice in speech and language therapy showcases the creative ways that SLTs are developing knowledge and skills for EBP, creating contexts that support the use of evidence in practice, and working towards making evidence easily accessible and usable. It includes real-life examples of how SLTs have encountered a clinical problem or situation and have accessed and used the evidence within their day-to-day practice. The contributors come from a wide range of work settings, from services situated within large organizations to those in independent practice, and represent a range of clinical areas, from paediatric to adult and across speech, language, voice, fluency, Augmentative and Alternative Communication (AAC), and dysphagia. This book is written for an audience of clinical practitioners, at any stage of their career, and is additionally a valuable resource for SLT students and lecturers.
Embedding Evidence-Based Practice in Speech and Language Therapy: International Examples; Contents; Contributors; Foreword; About the editors; Acknowledgements; Section One: Understanding EBP; Section Two: Developing knowledge and skills for EBP; Section Three: Creating a supportive context for EBP; Section Four: Making the evidence work for us; Section Five: Applying evidence to meet clinical challenges; Section Six: Future directions for EBP in speech and language therapy; Index.
Includes bibliographical references and index.
Print version record.
Keywords: Speech therapy; Evidence-Based Medicine; International cooperation; Evidence-based medicine; International cooperation; Speech therapy; Electronic books